Social health insurance scheme for all Kenyans: Opportunities and sustainability potential - Njeru, Enos H. N.; Arasa, Robert; Nguli, Mary (Institute of Policy Analysis and Research, 2004)
Health is a basic need for all, regardless of race, nationality, social class, age, sex, etc. In Kenya, just like in many other developing countries, the health situation has been deteriorating in spite of the government having since independence directed her efforts towards tackling the twin problems of affordability and access to health care services. Beyond this, the policy position is also clear on the need to address equity and sustainability of quality health care delivery. The health sector reforms that have hitherto taken place (including introduction of NI-HF, free health services, cost-sharing, exemptions and waivers, etc.) are all largely aimed at addressing affordability and access to health care services, especially among the poor. The latter often ﬁnd themselves in poverty traps that deny them access to social services, consequent upon which they benefit least from health, education, food security, knowledge and information services and other basic human rights components.